ORIGIN OF UPPER-MANTLE SEISMIC SCATTERING - EVIDENCE FROM RUSSIAN PEACEFUL NUCLEAR EXPLOSION DATA - Nielsen L.; Thybo H.; Levander A.; Solodilov L.N. (My University, 2003)
Detailed interpretation of upper-mantle scattered waves recorded in the 800-1400 km offset range of four reversed `peaceful nuclear explosion' seismic sections along the 3500 km long profile Kraton in Russia has revealed an similar to85 km thick seismically inhomogeneous low-velocity zone below the 8degrees discontinuity at similar to100 km depth. The scattered waves make up a wave train of high amplitude that decreases in duration from similar to8 s at 800 km offset to similar to4 s at 1400 km offset. 2-D elastic finite-difference modelling of the seismic wavefield has previously shown that the inhomogeneous zone from similar to100 to similar to185 km depth may be described by continuous, random velocity fluctuations represented by an exponential medium with a horizontal correlation length of 5-10 km, a vertical correlation length of 5 km and a standard deviation of similar to2 per cent of the average background velocity value. Here, we demonstrate that other proposed velocity fluctuations in the lower crust and in the uppermost mantle from the Moho to similar to100 km depth cannot explain the observed scattered phases. Our study shows that upper-mantle velocity fluctuations below the 8degrees discontinuity at 100 km depth are needed in order to explain the observed seismic wavefield, and that they lead to scattering that is significantly different from the scattering caused by the fluctuations at shallower levels.
Keywords: 8° discontinuity; scattering; seismic modelling; seismic waves; synthetic seismograms; upper mantle